Turkish transnational business professionals in Istanbul : globalization, cosmopolitanism and the emerging elite - İlhan, Deniz. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
The neo-liberal economic transformation that was initiated in post-1980s Turkey has produced a Turkey in the 2000s that has been integrated to the global economy through processes such as the liberalization of the markets, privatization and opening to transnational economic actors and financial instruments. In this manner, starting from the 1990s, the increase, growth and expansion of foreign and multinational corporations in Istanbul has made possible the emergence of new business people, who are more connected to the globe in their daily lives. These business people constitute a portion of a globally available population that has drawn the attention of academic and non-academic circles throughout the globe from 80’s onwards. In the international sociological literature, this population is regarded as the “transnational elite” of the global era and their members are described as people who are embedded in exclusive transnational social networks, who are globally mobile, who share a global business culture and as people who have exclusive consumption practices. As for the field research of this thesis, middle and high-ranking business professionals who are employed in foreign and multinational corporations in Istanbul which operate on regional/global levels were interviewed in-depth. In the thesis, these subjects are problematized as political and cultural members of localities and communities that straddle between the local and the global. Within the scope of the interviews, social relations and imaginations of these subjects were discussed through their personal histories and narratives regarding their “selves.” Moreover, their personal opinions regarding contemporary socio-political issues at different geographical levels were discussed. The aim of the thesis is to contextualize these subjects as national members of the secular Turkish elite and as the transnational members of the transnational professional elite. In this regard, it was discussed whether transnational exposure and experience contribute to the cultivation of cosmopolitan dispositions in regards to the public sphere. It has been observed that the use of socio-political typologies such as “white Turks,” “neo-Kemalists,” “Yuppies” that emphasize socio-political elitism/ indifference/hostility – although may proficiently describe many Turkish elite positions - oversees pluralist and egalitarian tendencies that can be cultivated within elite circles due to translocal interaction and exposure.
Keywords: International business enterprises -- Turkey -- Istanbul.; International officials and employees -- Turkey -- Istanbul.